Foreign policy of Serbia after the breakup of Yugoslavia: the search for allies (sketch of the problem) - Szczepański, Wojciech (Balcanica Posnaniensia. Acta et studia, 2022)
The aim of the article is to characterize generally main Serbian geopolitical strategies since the collapse of socialist Yugoslavia. In the changing global conditions, transforming from a Cold War-bipolar, into a multipolar order, Serbia has developed a concept of functioning in international politics and economy on four pillars: the European Union (EU), the United States (US), Russia and China. However, the Serbian elites are divided into two camps: pro-Western and pro-Russian. The advantage of the pro-Russian option, which has been visible for over a decade, is based on historical and cultural sentiments and the experience of hostility from the West, manifested during the Kosovo crisis period. However, in 2022, as a result of the military aggression of Russia against Ukraine, a gradual weakening of Serbian-Russian ties is possible in order to strengthen the position of Serbia on its way towards EU. The article is merely an introduction to main motives influencing Serbian foreign policy. It also notifies the role for Serbia of Turkey, China and other Asian countries.